Preventing mussel adhesion using lubricant-infused materials - Amini, Shahrouz; Kolle, Stefan; Petrone, Luigi; Ahanotu, Onyemaechi; Sunny, Steffi; Sutanto, Clarinda N.; Hoon, Shawn; Cohen, Lucas; Weaver, James C.; Aizenberg, Joanna; Vogel, Nicolas; Miserez, Ali (Science, 2017)
Mussels are opportunistic macrofouling organisms that can attach to most immersed solid surfaces, leading to serious economic and ecological consequences for the maritime and aquaculture industries. We demonstrate that lubricant-infused coatings exhibit very low preferential mussel attachment and ultralow adhesive strengths under both controlled laboratory conditions and in marine field studies. Detailed investigations across multiple length scales-from the molecular-scale characterization of deposited adhesive proteins to nanoscale contact mechanics to macroscale live observations-suggest that lubricant infusion considerably reduces fouling by deceiving the mechanosensing ability of mussels, deterring secretion of adhesive threads, and decreasing the molecular work of adhesion. Our study demonstrates that lubricant infusion represents an effective strategy to mitigate marine biofouling and provides insights into the physical mechanisms underlying adhesion prevention.